Risk Factors of Psychological Responses of Chinese University Students During the COVID-19 Outbreak: Cross-sectional Web-Based Survey Study - Xudong Zhang; Xin Shi; Yang Wang; Huiquan Jing; Qingqing Zhai; Kunhang Li; Dan Zhao; Shiyu Zhong; Yuequn Song; Feng Zhang; Yijun Bao (JMIR Publications, 2021)
BackgroundCOVID-19 is a highly contagious and highly pathogenic disease caused by a novel coronavirus, SARS-CoV-2, and it has become a pandemic. As a vulnerable population, university students are at high risk during the epidemic, as they have high mobility and often overlook the severity of the disease because they receive incomplete information about the epidemic. In addition to the risk of death from infection, the epidemic has placed substantial psychological pressure on the public. In this respect, university students are more prone to psychological problems induced by the epidemic compared to the general population because for most students, university life is their first time outside the structure of the family, and their mental development is still immature. Internal and external expectations and academic stress lead to excessive pressure on students, and unhealthy lifestyles also deteriorate their mental health. The outbreak of COVID-19 was a significant social event, and it could potentially have a great impact on the life and the mental health of university students. Therefore, it is of importance to investigate university students' mental health status during the outbreak of COVID-19. ObjectiveThe principal objective of this study was to investigate the influencing factors of the psychological responses of Chinese university students during the COVID-19 outbreak. MethodsThis study used data from a survey conducted in China between February 21 and 24, 2020, and the data set contains demographic information and psychological measures including the Self-Rating Anxiety Scale, the Self-Rating Depression Scale, and the compulsive behaviors portion of the Yale-Brown Obsessive-Compulsive Scale. A total of 2284 questionnaires were returned, and 2270 of them were valid and were used for analysis. The Mann-Whitney U test for two independent samples and binary logistic regression models were used for statistical analysis. ResultsOur study surveyed 563 medical students and 1707 nonmedical students. Among them, 251/2270 students (11.06%) had mental health issues. The results showed that contact history of similar infectious disease (odds ratio [OR] 3.363, P=.02), past medical history (OR 3.282, P<.001), and compulsive behaviors (OR 3.525, P<.001) contributed to the risk of mental health issues. Older students (OR 0.928, P=.02), regular daily life during the epidemic outbreak (OR 0.410, P<.001), exercise during the epidemic outbreak (OR 0.456, P<.001), and concern related to COVID-19 (OR 0.638, P=.002) were protective factors for mental health issues. ConclusionsAccording to the study results, mental health issues have seriously affected university students, and our results are beneficial for identifying groups of university students who are at risk for possible mental health issues so that universities and families can prevent or intervene in the development of potential mental health issues at the early stage of their development.